Multiple Developmental Dental Anomalies in a Non-Syndromic Patient: Report of a Rare Simultaneous Occurrence - Maryam Ghasempour; Samane Hemmati; Samane Gharekhani; Ehsan Mooudi (Tehran University of Medical Sciences, 2016)
A case of multiple pulp stones, a supernumerary tooth and a congenitally missed tooth accompanied by several developmental dental anomalies concurrently affect- ing the upper and lower anterior teeth in an Iranian healthy girl is reported. Devel- opmental tooth abnormalities are usually found in conjunction with certain diseases or conditions. In the present case, although the patient had consanguineous parents and the role of genetics should be considered particularly for autosomal recessive traits, based on the child's family and medical history, no correlation could be es- tablished between dental findings and systemic or metabolic diseases.